From metaphysical representations to aesthetic life : toward the encounter with the other in the perspective of Daoism - Lacertosa, Massimiliano, 1980- (SUNY series in Chinese philosophy and culture., 2023)
Reevaluates Western and Chinese philosophical traditions to question the boundaries of entrenched conceptual frameworks.